2011
DOI: 10.1002/msj.20279
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's Disease: Diagnosis and Treatment Across the Spectrum of Disease Severity

Abstract: Alzheimer’s disease exists along a spectrum, from early memory changes to functional dependence and death. Using a case illustration, we review the evaluation and diagnosis of mild cognitive impairment and the diagnosis and management of Alzheimer’s disease at each stage, including the management of both cognitive and behavioral/psychiatric aspects of the disease and end-stage and end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 40 publications
0
61
0
1
Order By: Relevance
“…Further, the magnitude of the reduction in cholinergic system activity is correlated with the degree of cognitive impairment (Francis, Palmer, Snape, & Wilcock, 1999). Geriatric mild cognitive impairment is characterized by episodic memory impairment such as forgetting details of a recently viewed movie or conversations (Neugroschl & Wang, 2011). At early stages of AD, the cholinergic failure is also mild, and the impairment includes forgetting of daily events such as paying bills or taking medications (Neugroschl & Wang, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, the magnitude of the reduction in cholinergic system activity is correlated with the degree of cognitive impairment (Francis, Palmer, Snape, & Wilcock, 1999). Geriatric mild cognitive impairment is characterized by episodic memory impairment such as forgetting details of a recently viewed movie or conversations (Neugroschl & Wang, 2011). At early stages of AD, the cholinergic failure is also mild, and the impairment includes forgetting of daily events such as paying bills or taking medications (Neugroschl & Wang, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Geriatric mild cognitive impairment is characterized by episodic memory impairment such as forgetting details of a recently viewed movie or conversations (Neugroschl & Wang, 2011). At early stages of AD, the cholinergic failure is also mild, and the impairment includes forgetting of daily events such as paying bills or taking medications (Neugroschl & Wang, 2011). On the contrary, at advanced stages of AD, the cholinergic dysfunction is profound, and there is also an important loss of cortical neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calleo et al [19] reported that 43% of the patients with AD and anxiety who had a Neuropsychiatric Inventory score for anxiety of more than 4 points met the criteria for GAD. Some reports indicated that treatments for anxiety disorder, including short-acting benzodiazepine or cognitive behavioral therapy, were also effective for the treatment of anxiety in AD [20,21,22]. However, a consensus on how to define anxiety in dementia, including AD, has not yet been achieved [16].…”
Section: Introductionmentioning
confidence: 99%
“…27 The present consensus states that MCI is characterized by clinical heterogeneity and that it includes amnestic (consisting of memory problems) and non-amnestic (consisting of impairment in other cognitive domains) phenotypes accompanied by subtypes of single and multiple domain classifications. 28,29 Prevalence rates of MCI in population-based studies including participants aged 60 and over, range between three percent and 19 percent, with higher rates associated with increasing age and lower education, [29][30][31] reaching even 42 percent among those aged 85 and above. 32 A recent systematic review of nine studies assessing the incidence of MCI showed the incidence of amnestic MCI to range between 28 and 36 per 1,000 person-years and the incidence for any type of MCI to range between 51 and 77 per 1,000 person-years.…”
Section: Definition and Epidemiologymentioning
confidence: 99%